2023
DOI: 10.3389/fneur.2023.1226591
|View full text |Cite
|
Sign up to set email alerts
|

Real-world efficacy and tolerability of fremanezumab in adults with chronic migraine: a 3-month, single-center, prospective, observational study

Abstract: BackgroundFollowing the promising pre-marketing placebo-controlled randomized clinical trials of fremanezumab, post-marketing studies are necessary to verify efficacy and tolerability in various real-world settings. The present study assessed real-world efficacy and safety of fremanezumab.MethodsA 3-month, single-center, prospective, observation study of adults with chronic migraine who were treated with monthly subcutaneous injections of 225 mg fremanezumab in Denmark. The primary outcome was defined as propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…This study compares favourably with similar studies in other academic centres. Argyriou et al, who also reported a cohort of patients with at least three preventative treatment failures, reported a ≥50% reducation in MHD at 3 months of 62.6%, with similar reports by Cullum et al 17 18 Iannone et al reported lower rates of treatment continuation at 12 months compared with our cohort. 19 The reported adverse event rate varies in the literature between 19.5% and 73.3%, 2 13 20 with similar reported events.…”
Section: Discussionsupporting
confidence: 90%
“…This study compares favourably with similar studies in other academic centres. Argyriou et al, who also reported a cohort of patients with at least three preventative treatment failures, reported a ≥50% reducation in MHD at 3 months of 62.6%, with similar reports by Cullum et al 17 18 Iannone et al reported lower rates of treatment continuation at 12 months compared with our cohort. 19 The reported adverse event rate varies in the literature between 19.5% and 73.3%, 2 13 20 with similar reported events.…”
Section: Discussionsupporting
confidence: 90%